The Fourfold Gospel, Volume 1: A Formational Commentary on Matthew, Mark, Luke, and John: From the Beginning to the Baptist - DelHousaye, John (Wipf and Stock Publishers, 2020)
Intro -- Title Page -- Preface -- Acknowledgments -- Abbreviations -- Entering the Gospels -- Beginnings -- Birth -- Baptism -- Bibliography.